2015
DOI: 10.1177/1934578x1501000670
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Chemical Composition and Antioxidant Properties of the Essential Oils of three Sideritis libanotica Subspecies

Abstract: The phytochemical composition of the essential oils of three Sideritis libanotica subspecies, namely S. libanotica ssp. libanotica, S. libanotica ssp. linearis and S. libanotica ssp. michroclamys, all collected in Lebanon, was analyzed by GC and GC-MS. The diterpene sideridiol was recognized as the main constituent of both S. libanotica ssp. libanotica (50.8%) and S. libanotica ssp. michroclamys (18.4%) oils, while hexadecanoic acid (10.5%) prevailed in S. libanotica ssp. linearis. The antioxidant activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The anti-hypercholesterolemic effects of Sideritis hyssopifolia has been demonstrated in this study for the first time. Other authors have demonstrated the antioxidant properties of different Sideritis species [52,53] as well as their lowering effect on triglycerides [54]. The antioxidant activity found for these species was intermediate, as our results indicate for Sideritis hyssopifolia , L. This antioxidant activity has been related mainly to their content in polyphenols.…”
Section: Discussionsupporting
confidence: 57%
“…The anti-hypercholesterolemic effects of Sideritis hyssopifolia has been demonstrated in this study for the first time. Other authors have demonstrated the antioxidant properties of different Sideritis species [52,53] as well as their lowering effect on triglycerides [54]. The antioxidant activity found for these species was intermediate, as our results indicate for Sideritis hyssopifolia , L. This antioxidant activity has been related mainly to their content in polyphenols.…”
Section: Discussionsupporting
confidence: 57%
“…Cold, flu, pharyngitis, pleasure, as tea (Demirel, 2021;Bulut et al, 2017;Demirci, Özhatay, 2012;Bulut, Tuzlacı, 2015;Kocabaş, Gedik, 2016;Tanaydın, 2021;Arasan, 2022) Antimicrobial, Antifeedant, Antifungical, (Dulger et al, 2006;Bondi et al, 2000) β-pinene (Kirimer et al, 1999) S Güvenc et al, 2005;Loğoğlu et al, 2006;Aligiannis et al, 2001;Gergis et al, 1991) β-myrcene (Maškovic et al, 2023) S. stricta Aladaglar/Nigde Aerial parts Infusion Cold, flu (Akgül et al, 2016;Sarı et al, 2010) Antimicrobial, Alzheimer's disease, Parkinson's disease, Anti-inflammatory, Analgesic Kılıç, 2006;Turkmenoglu et al, 2015; β-pinene (Sattar, 1995) S. syriaca subsp. nusairiensis…”
Section: S Rubrifloramentioning
confidence: 99%
“…Cold (Güzel et al, 2015;Kocabaş, Gedik, 2016;Altay et al, 2015;Varlıbaş-Odunkıran, 2020;Özer, Türkmen, 2019) Antiviral, Antimicrobial, Antioxidant, Analgesic, Antiinflamatory (Sattar, 1995;Koutsaviti et al, 2013;Goulas et al, 2014;Karapandzova et al, 2013;Menghini et al, 2005) α-pinene )…”
Section: Aerial Parts Unspecifiedmentioning
confidence: 99%
“…The genus Sideritis L., which includes nearly 150 species, is one of the largest of the Lamiaceae family. The members of this genus are distributed worldwide, mostly in the Mediterranean basin [1][2][3]. Sideritis sp.…”
mentioning
confidence: 99%